The Analysis of the Rise and Fall of Globalization - Sertif DEMİR; R. Dilek KOÇAK (Gazi Akademik Bakış)
Globalization is a term explaining the increasing connectivity and cross-border activity among nations in economic, business, trade, tourism, migration, and cultural activities. Globalization has been the most contentious concept that has been evaluated according to political biases and national interests. Therefore, this paper aims at analyzing globalization in context of conceptual evolution, dynamics and factors enlarging globalization, the evaluatıon of globalization and finally the reasons for the decline of globalization. Covid 19 pandemic and its interaction with globalization will also be scrutinized as well. The major outcome of the study sets forth that the actual evolution of globalization has taken place with capitalist progress. It has been a major force in the further progress of globalization Although we are in a declining process of globalization, it is clear that it will survive with humanity as long as human beings exist.